Challenges and opportunities in health care and nursing management research in times of COVID-19 outbreak - Palese, Alvisa; Papastavrou, Evridiki; Sermeus, Walter (My University, 2021)
Aim To reflect upon the concrete implications of the COVID-19 outbreak regarding ongoing health service and nursing management research (NMR) and to identify possible research priorities for the current and post-pandemic era. Background Health service research and the nursing management research debate have received little attention to date, despite their relevance in responding to the increased demand of care during the COVID-19 outbreak. Methods A critical analysis on experiences was performed while leading international-funded studies at different degrees of complexity and targets, involving nurse managers, nurses, care processes and health care services in the last year. Results Ongoing research projects have been profoundly affected by the COVID-19 outbreak in their aims, methods, management processes, feasibility and outcomes. Conclusions The COVID-19 outbreak is an unprecedented stress test for the health care sector and for the nursing services. Its onset and persistence have rendered more easily to see what prevails in terms of effectiveness and what fails in our health care services. Implications for Nursing Management Nurse managers have lived and are still living through this crisis, given their omnipresence in the health care systems. Therefore, setting NMR priorities and working together to imagine and design the post-COVID-19 era is essential.
Keywords: COVID-19; Health service research; Implications; Nursing management research; Priorities